An assessment of students' acceptance and usage of computer supported collaborative classrooms in hospitality and tourism schools. (June 2016) - Ali, Faizan; Nair, Pradeep Kumar; Hussain, Kashif
Abstract: Technological advancements have become important feature of hospitality and tourism educational plans to improve learning experiences of students within schools. It is vital for these schools to assess if technologies do influence the perceptions and behaviour of their target beneficiaries. This study aims to explain the factors affecting students' acceptance and usage of computer supported collaborative classrooms in a hospitality and tourism school based on the Extended Unified Theory of Acceptance and Use of Technology (UTAUT2) model. The study is established using causal research design in order to examine the cause-effect relationship between the study variables. Sample of the study consists of 222 students recruited via campus email as respondents. Data is collected using a five-point Likert scale covering UTAUT2's factors and variables featuring acceptance and usage of computer supported collaborative classrooms. Partial least squares based structural equation modelling is used to analyse the data. Findings show that performance expectancy, effort expectancy, social influence, facilitating conditions, price-value, hedonic motivation and habit have significant influence on students' acceptance and usage of these computer supported collaborative classrooms. Responding to the need of studies validating the UTAUT2 model in the adoption and use of different technologies, this study contributes to the literature by extending the UTAUT2 into the context of computer supported collaborative classrooms. These results also provide a useful framework for hospitality and tourism schools to successfully implement experience-enhancing technologies such as computer supported collaborative classrooms. Graphical abstract: